Can Compassion Transform Our Dying? A Reading of Compassion for Palliative and End-of-Life Care. Issue 2 (2nd July 2016) - Larkin, Philip J.
Abstract : This paper is based on a keynote presentation given at the Annual Conference of the British Association for the Study of Spirituality in May 2016. It claims that compassion is core to the way in which palliative and end-of-life care is delivered; and argues that compassion is not simply a feeling or emotion but is an action with physical, psychosocial and spiritual properties. It points out that, without compassion, the risks to the care of the dying are great, as evidenced in recent UK government reports. Compassionate care for dying people requires not only clinical excellence but the practitioner's understanding of love and service - and of themselves.